Cytotoxic, antioxidant, antimicrobial properties and chemical composition of rose petals. (2nd August 2013) - Nowak, Renata; Olech, Marta; Pecio, Łukasz; Oleszek, Wiesław; Los, Renata; Malm, Anna; Rzymowska, Jolanta
Abstract BACKGROUND Rosa rugosa petals are used for production of teas, jams, wines and juices. Despite the wide availability of rose cultivars, comprehensive information on petal chemical composition and healthful properties is still lacking. Therefore, the aim of this study was analysis of cytotoxic, antioxidant and antimicrobial activity and chemical composition of rugosa rose petals. RESULTS Petals of R. rugosa were evaluated for their cytotoxic effect against cervical (HeLa) and breast cancer (T47D) cell lines and for antiradical activity (with DPPH). As a result, significant cytotoxic (up to 100% of dead cells) and antiradical properties (IC50 1.33–0.08 mg mg−1 DPPH) were demonstrated. Moreover, notable antimicrobial activity against eight bacterial (i.e. Staphylococcus. epidermidis, S. aureus, Bacillus subtilis, Micrococcus luteus, Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Proteus mirabilis) and two yeast strains (Candida. albicans, C. parapsilosis) was shown. Total phenolic, flavonoid, phenolic acid, tannin, carotenoid and polysaccharide content in petals was determined using spectrophotometric methods. Liquid chromatography–electrospray ionization–tandem mass spectrometry was used to thoroughly analyze phenolic acids and flavonoid glycosides in the methanolic extract and fractions obtained after its separation. Five phenolic acids and six flavonoids previously not reported in the plant material were identified. CONCLUSION This is the first such detailed report on chemical composition and biological activity of R. rugosa petals. © 2013 Society of Chemical Industry